Kualitas dan Daya Simpan Ikan Kakap Merah dengan Daun Anting-anting (Acalypha indica L.) sebagai Pengawet Alami - Sofian, Mochamad, Dra. Titik Suryani, M.Sc (2017)
The red snapper is a saltwater fish that has a moisture content of 77.53%, 20.55% protein, 0.27% fat and 0.23% carbohydrates. Quality red snapper will be reduced due to the activity of microorganisms that need preservation. The active compounds in the leaf of anting-anting are alkaloids, catachol, flavonoids, phenolic compounds, saponins and steroids can be used as a natural preservative to inhibit microbial activity. The purpose of this study to determine the number of colonies of bacteria, moisture content, pH, organoleptic test, the quality and shelf life of red snapper. The research method using a completely randomized design (CRD) with two factors, one is heavy anting-anting leaf (40g + 100ml of aquades, 50g + 100ml of aquades, 60g + 100ml of aquades) and the second factor is soaking time (S1= 30' , S2= 60'). The results showed the best quality red snapper in the treatment of M3S2 (Anting-anting leaf 60g + 100ml of aquades and 60' of immersion) with the number of bacterial colonies was 2.64 x 106 cfu / g, water content 53.8% and a pH of 6 with the appearance of red bright, fresh scent anting-anting leaf, solid and pliable texture, color brownish red gills, eyes bulging and the shelf life of less than 18 hours and still be consumed.